Demandes d’asile à la frontière américano-canadienne : l’Entente entre le Canada et les États-Unis sur les tiers pays sûrs et les valeurs canadiennes - Laurence Cros (Institut des Amériques, 2021)
This article intends to offer an update on what the current debate on the Canada-United States Safe Third Country Agreement (STCA) reveals about Canadian policy regarding asylum seekers who enter the country at its only land border, and how this policy is consistent with Canadian values. This article will borrow from the approach of liberal realism to understand the disconnect that exists between a discourse that emphasizes the values ​​of welcome and compassion, and a diplomatic and migratory practice that seems to favor the limitation of asylum requests at Canada’s only land border.